Targeting Tumor Growth and Progression in Carcinoma Prevention through Natural Catechol as Chemo Preventive Agents - Krishna, Siddhant; Chatterjee, Sandip; Goswami, Pawan Kumar (Pharmacognosy Reviews)
Green tea is rich in catechins, which are polyphenolic chemicals that have strong anticancer effects through pro-apoptotic, anti-inflammatory, and antioxidant processes. They alter a number of molecular pathways, including as those that control the course of the cell cycle, limit angiogenesis, and reduce metastasis. With traditional Chemotherapeutics, Epigallocatechin Gallate (EGCG), the most researched catechin, exhibits synergistic actions that increase efficacy and decrease toxicity. Catechins may serve as both preventive and therapeutic agents in the treatment of carcinoma, according to data from in vitro, in vivo, and a small number of clinical investigations. However, issues like poor absorption and varying patient reactions call for sophisticated administration methods and extensive clinical testing.
Keywords: Angiogenesis; Apoptosis; Bioavailability; Cancer prevention; Cancer therapy; Carcinoma; Catechins; Epigallocatechin gallate; Green tea; Metastasis.